Sarcoid-Like Mediastinal Lymphadenopathy in Gynecologic Malignancy - Lashari, Bilal H.; Asai, Megumi; Randleman, Gissele; Sack, Martha; Patel, Rajeshkumar (Pulmonary Medicine, 2018)
Noncaseating granulomas are seen surrounding tumors with varying frequency, possibly as part of an immune response to tumor cells. However, data about the association of sarcoid with gynecologic malignancy is sparse. We performed a search of our institutional database for all EBUS-TBNA biopsies conducted within the past five years that revealed granulomatous inflammation. All adult female patients with a history of gynecologic malignancy were included. Patients with a history of sarcoidosis or fungal or mycobacterial infection were excluded. All patients with evidence of malignant cells on TBNA specimen were excluded. Our results revealed 65 patients with histologic diagnosis of a noncaseating granuloma on EBUS-TBNA. Five patients (7.69%) had a history of gynecologic malignancy. Two patients had evidence of PET-positive nodes on surveillance scans, which led directly to the examination. Our findings suggest that distant malignancies may cause granulomatous lymphadenitis, through yet undefined mechanisms. As such, patients with evidence of mediastinal lymphadenopathy could benefit from routine sampling and histologic examination to define the pathology in the correct clinical context.